IMPLEMENTASI FUZZY INFERENCE SYSTEM METODE TSUKAMOTO PADA PENGAMBILAN KEPUTUSAN PEMBERIAN KREDIT PEMILIKAN RUMAH - Wilis Kaswidjanti (Jurusan Teknik Informatika, 2014)
Competition in today's banking world is getting heavier and tighter. This is because theproducts of the bank with the other banks can be said to be the same. So the competition forgood customers to obtain product deposits and loans (mortgages) increasingly difficult. But thebanking world are now widely utilize information technology to banking activities. One of the useof information technology is the use of decision support applications for granting loans(mortgages). The method used in the decision support system is a Fuzzy Inference System(FIS) to determine the calculation method of Tsukamoto decision. The implementation of thisapplication is more emphasis on the decision-making process for granting to produce a decisionissued.Keywords: Decision Support Systems, Home Ownership Credit (KPR), Fuzzy InferenceSystem (FIS) Tsukamoto method